Komparasi Kinerja Pegawai Negeri Sipil (PNS) dengan Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) - Nadia, Rahma; Suhartono, S (Journal of Economics and Management Scienties, 2024)
The government has 2 types of employment as its main Human Resources (HR), namely Civil Servants (PNS) and Government Employees with Work Agreements (PPPK). This HR element is very important in organizational performance. The achievement factor of organizational goals is influenced by the quality and competence of the HR owned. Low quality HR can hinder performance which has an impact on the decline of the organization in achieving its goals. This study aims to compare the performance and differences between PNS and PPPK at the Bina Karya and Laras Social Rehabilitation Center. The method used in this study is quantitative with a comparative study type. The data collection techniques used are observation and questionnaires. The sample used was 17 Civil Servants (PNS) and 17 Government Employees with Work Agreements (PPPK) at the Bina Karya and Laras Social Rehabilitation Center of the Yogyakarta Provincial Social Service. The results of the study were that there was no significant difference between the performance of PNS and PPPK. So these two types of employment do not affect organizational performance.